Potential of novel food-borne Lactobacillus isolates against the honeybee pathogen Paenibacillus larvae. Issue 9 (1st September 2020) - Lazzeri, Anna Marta; Mangia, Nicoletta P.; Mura, Maria Elena; Floris, Ignazio; Satta, Alberto; Ruiu, Luca
ABSTRACT: An in vitro study was conducted to screen for the inhibitory potential of lactic acid bacteria (LAB), isolated from fermented food matrices, against the honeybee American Foulbrood agent Paenibacillus larvae . Various strains of Lactobacillus plantarum showed significant antagonism associated with their cell-free culture supernatant (CFS). The characterisation of this inhibition was based on assays and analyses involving different fraction and extracts. A significant effect was associated with media acidification resulting from LAB growth. However, this antimicrobial activity was found to be heat-stable and specific experiments suggested the implication of small antimicrobial peptides and/or antibiotics. Accordingly, a possible role of plantaricins released by L. plantarum in the culture supernatant was confirmed by the expression of different plantaricin-related genes. The results obtained in this study support further investigations on LAB strains as biological control agents for application in the apiary to preserve and improve honeybee health.